Crystal structures of human ETB receptor provide mechanistic insight into receptor activation and partial activation. Issue 1 (December 2018) - Shihoya, Wataru; Izume, Tamaki; Inoue, Asuka; Yamashita, Keitaro; Kadji, Francois; Hirata, Kunio; Aoki, Junken; Nishizawa, Tomohiro; Nureki, Osamu
Abstract Endothelin receptors (ETA and ETB ) are class A GPCRs activated by vasoactive peptide endothelins, and are involved in blood pressure regulation. ETB -selective signalling induces vasorelaxation, and thus selective ETB agonists are expected to be utilized for improved anti-tumour drug delivery and neuroprotection. Here, we report the crystal structures of human ETB receptor in complex with ETB -selective agonist, endothelin-3 and an ETB -selective endothelin analogue IRL1620. The structure of the endothelin-3-bound receptor reveals that the disruption of water-mediated interactions between W6.48 and D2.50 is critical for receptor activation, while these hydrogen-bonding interactions are partially preserved in the IRL1620-bound structure. Consistently, functional analysis reveals the partial agonistic effect of IRL1620. The current findings clarify the detailed molecular mechanism for the coupling between the orthosteric pocket and the G-protein binding, and the partial agonistic effect of IRL1620, thus paving the way for the design of improved agonistic drugs targeting ETB . Signalling through the endothelin receptor ETB, a class A GPCR, induces nitric oxide-mediated vasorelaxation. Here the authors present the crystal structures of the human ETB receptor bound to the peptide hormone endothelin-3 and in complex with the ETB -selective partial agonist IRL1620 and discuss mechanistic implications for receptor activation.